STING is dispensable during KSHV infection of primary endothelial cells - Vogt, Daniel (Virology, 2019)
During DNA virus infections, detection of cytosolic DNA by the cGAS-STING pathway leads to activation of IFN-β. Kaposi’s Sarcoma Herpesvirus (KSHV), an oncogenic DNA virus, is the etiological agent of Kaposi’s Sarcoma, an endothelial cell (EC)-based tumor. To investigate the role of STING during KSHV infection of primary ECs we identified a primary lymphatic EC sample that is defective for STING activation and we also knocked out STING in blood ECs. Ablation of STING in EC does not increase susceptibility to KSHV latent infection nor does it increase KSHV spread after lytic reactivation indicating STING signaling does not restrict KSHV. In contrast, STING ablation increases Adenovirus spread at low MOI, but STING is dispensable for blocking replication. These experiments reveal that the importance of STING depends on the DNA virus and that STING appears more important for restricting spread to bystander cells than for inhibition of viral replication.